Linguistic Fluency Among Fifth-Grade Students According to Playing Electronic Games "A Field Study in the Schools of the First Cycle of Basic Education in Lattakia" - حاتم, عبير (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The research aimed to determine the effect of playing electronic games on linguistic fluency in children، and determine the differences in linguistic fluency between these children according to gender. The sample of the study consisted of (110) children from the fifth-grade students (38 male / 72 female)، the sample was divided into two groups (the first: Students who do not play electronic games) and (the second: Students who play electronic games). To achieve this aims، the researcher used the descriptive research methodology، and the measure of innovative thinking that consists of four parts: Two parts for verbal fluency and two parts for intellectual fluency. The study showed the following results: - There are differences in the level of the linguistic fluency among the fifth-grade students according to gender، in favor of female. - There are differences in the level of linguistic fluency between the first and second groups on the linguistic fluency scale، in favor of members of the first group and of both sexes.